The Physicochemical, Biopharmaceutical, and In Vitro Efficacy Properties of Freeze-Dried Dexamethasone-Loaded Lipomers - Eloy Pena-Rodríguez; Aida Mata-Ventosa; Laura Garcia-Vega; Sandra Pérez-Torras; Francisco Fernández-Campos (Pharmaceutics, 2021)
Dexamethasone-loaded polymer hybrid nanoparticles were developed as a potential tool to treat alopecia areata due to their follicular targeting ability. Freeze drying (FD) is a common technique used to improve nanoparticle stability; however, there are few studies focused on its effect on ethyl cellulose lipid-core nanoparticles. Nanoparticles were lyophilized with different cryoprotectants. Sucrose was selected because it allowed for a good resuspension and provided acceptable physicochemical parameters (374.33 nm, +34.7 mV, polydispersion 0.229%, and 98.87% encapsulation efficiency). The nanoparticles obtained were loaded into a pleasant xanthan gum hydrogel, and the rheological, release, and skin permeation profiles of different formulations were studied. The FD formulation significantly modified the particle size, and the drug release and permeation properties were also altered. In addition, analyses of the cytotoxicity and anti-inflammatory efficacy of FD and non-FD particles on human keratinocytes indicated no differences.